Macroeconomic Implications for Hong Kong SAR of Accommodative U.S. Monetary Policy - N'Diaye, Papa. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses the potential macroeconomic implications for Hong Kong SAR of accommodative monetary policy in the United States. It shows, through model simulations, that a resumption of the credit channel in Hong Kong SAR has the potential to create inflation in both goods and asset markets. Expansionary financial conditions will likely have a greater impact in fueling asset price inflation, manifested in the model through a strong increase in equity prices. Higher asset prices could, in turn, through a financial accelerator mechanism, lead to further credit expansion and an upward cycle of asset prices and credit. This cycle, if unchecked, can potentially feed into volatility in consumption, output and employment and complicate macroeconomic management. The simulation results suggest there is a role for countercyclical prudential regulations to mitigate the amplitude of the cycle and lessen the financial and macroeconomic volatility associated with an unwinding of the credit-asset price cycle.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet